High-Intensity Interval Training in Normobaric Hypoxia Improves Cardiorespiratory Fitness in Overweight Chinese Young Women - Kong, Zhaowei; Shi, Qingde; Nie, Jinlei; Tong, Tomas K.; Song, Lili; Yi, Longyan; Hu, Yang (Frontiers in Physiology, 2017)
Previous studies have investigated the effects of high-intensity interval training (HIIT) on cardiorespiratory fitness and body composition in overweight populations. However, the additive effect of HIIT and hypoxia on health parameters is not clear. This study compared the effects of HIIT under hypoxic conditions on cardiometabolic function with that under normoxia in overweight Chinese young women. Methods: A double-blind randomized controlled experimental design was applied. Twenty-four sedentary overweight Chinese young women (weight: 68.8 ± 7.0 kg, BMI: 25.8 ± 2.3 kg·m−2) participated in the HIIT under either normoxia (NORM, n = 13, PIO2: 150 mmHg, FIO2: 0.21) or normobaric hypoxia (HYP, n = 11, PIO2: 117 mmHg, FIO2: 0.15) for 5 weeks. HIIT was composed of 60 repetitions of 8 s maximal cycling effort interspersed with 12-s recovery per day, for 4 days per week. Cardiorespiratory fitness [peak oxygen uptake (V·O2peak), and peak oxygen pulse (peak O2 pulse)], serum lipid profile [triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C)], and body composition (regional and whole-body), were assessed at pre- and post-intervention during the days beyond the self-reported menstrual phase of the participants. Habitual physical activity and diary behavior were maintained during the intervention period. Results: With similar daily energy intake and physical activity, the increases in V·O2peak [NORM: 0.26 ± 0.37 L·min−1 (+11.8%) vs. HYP: 0.54 ± 0.34 L·min−1 (+26.1%)] and peak O2 pulse (NORM: +13.4% vs. HYP: +25.9%) for HYP were twice-larger than for NORM (p < 0.05). Although the 5-wk HIIT led to significant improvements in the ratios of TC/HDL-C (p = 0.035) and TG/HDL-C (p = 0.027), no significant group effects were found on the serum variables. Further, no significant changes in body composition or serum fasting leptin were observed in either group. Conclusion: 5-wk of HIIT improved cardiorespiratory fitness and blood lipids in overweight Chinese young females, while the additive effect of the HIIT under normobaric hypoxia solely enhanced cardiorespiratory fitness, but not body composition or serum lipid profile.